Peranan Modal Sosial dalam Pencegahan dan Penanganan Masalah Intoleransi di Nusa Tenggara Timur - Robert Mirsel; Felix Baghi; Puplius Meinrad Buru (Jurnal Ledalero, 2023)
This article focuses on identifying social capitals in preventing and handling religious intolerance in West Sumbaand Belu Regencies of NTT Province. Using qualitative approach, descriptive analysis, and employing interviews,and focused group discussions as methods of data collection, this study found that social capitals play a very crucialrole as social bounding in all communities in the three regencies. These social capitals include values such asopenness and willingness to accept others and differences, upholding unity and brotherhood, and traditional norms,customs (including kinship ties), symbols and language; the role of religious leaders, community leaders, traditionalleaders, interreligious harmony forums (FKUB), and youth forums. All of these social capitals become a force thatstrengthens tolerance and prevents intolerance in the three regencies. The implication is that Indonesia as a wholeand other parts of Indonesia can identify and use social capitals to strengthen tolerance and prevent intoleranceamong the people living in multicultural context.Keywords: social capital, intolerance prevention, social bonding, social bridging, social linking.